Analisis stratigrafi awal kegiatan Gunung Api Gajahdangak di daerah Bulu, Sukoharjo; Implikasinya terhadap stratigrafi batuan gunung api di Pegunungan Selatan, Jawa Tengah - Hill Gendoet Hartono; Sutikno Bronto (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20091Generally, Tertiary volcanisms in the Southern Mountains, Central Jawa were started with the formation of pillow lavas having basalt to basaltic andesite in composition. This initial stage volcanism developed into a  construction period of composite volcanoes that consist of alternating basaltic to andesitic lava flows, breccias, and tuffs. The construction period could be followed by a destructive phase, producing pumice-rich pyroclastic breccias, lapillistones, and tuffs of high silica andesite to dacite, or even rhyolite in composition. A stratigraphic measuring section at Bulu area, Sukoharjo Regency, presents an alternat- ing fine-grained andesitic volcaniclastic material and some limestones, with the total thickness is 143.33 m. The thickness of bedded volcaniclastic material tends to be thickening upward from 35 m until 90 m. The grain size of the volcaniclastic material also tends to be coarsening upward from clay size through silt and fine sand to coarse sand and granules. Paleontological analysis on fossils contained in the lime- stone gives an age of Early Miocene (N7 - N9). The volcaniclastic rocks is conformably overlain by the Mandalika Formation, comprising alternating andesitic breccias, lavas, and tuffs. These data imply that the fine-grained volcaniclastic material is an initial product of the construction period of Gajahdangak Volcano in the area, that formed the Mandalika Formation. This Formation is overlain by the Semilir Formation, composed of pumice-rich pyroclastic breccias and tuffs with dacitic composition. This as- sociated volcanic rock reflects a product of a caldera explosion or a destructive phase. Based on the characteristics of lithology of volcanic products from the initial stage, to a construction and destruction period, and compiled age data, the Southern Mountains represent formal volcanic rock units that are able to be divided into many formations.